Sensing properties of CdS-doped tin oxide thick film gas sensor - Yadava L.; Verma R.; Dwivedi R. (My University, 2025)
The tin oxide (SnO2) thick film gas sensor is fabricated by employing screen-printing technology. This pure SnO2 thick film is doped with 1 or 2 wt% of cadmium sulphide (CdS) by its weight and, thereby, the effect of dopant is presented. X-ray diffraction (XRD) analyses are administrated, which suggest that CdS dopant inhibits the crystallite growth leading to nanometric reduction in grain size. The fabricated gas sensor is responsively studied on exposure to liquid petroleum gas (LPG), methanol, and acetone. It is observed that CdS (2 wt%) doped structure exhibited highest response and is more selective to methanol (70 for 5000 ppm) over LPG and acetone at the operating temperature 200 °C. The CdS-doping improved response- and recovery-time from 90 s and 200 s, for undoped-film, to 40 s and 110 s for methanol (5000 ppm at 200 °C). © 2009 Elsevier B.V. All rights reserved.